Методы математической физики. Асимптотические методы учебное пособие - Багров физик профессор Томского государственного университета; Белов; Задорожный математик доцент Томского политехнического университета, кандидат физико-математических наук; Трифонов российский физик, математик профессор Томского политехнического университета, доктор физико-математических наук (Изд-во ТПУ, 2012)
This textbook presents supplementary chapters to the course "Methods of Mathematical Physics" and contains a material on special sections of this course: the canonical Maslov operator method and the complex WKB-Maslov method with its quantum-mechanical applications. The textbook can be useful to the graduate students, magisters, and post-graduates specializing in theoretical and mathematical physics. The textbook can be useful to the graduate students, magisters, and postgraduates specializing in theoretical and mathematical physics. The textbook is intended for students and post-graduates of physical and engineering departments.